About formulation of nitrilebutadiene rubber adhesives with a constant stickiness - L. R. Lyusova; A. Yu. Selina; Yu. A. Naumova (Тонкие химические технологии, 2012)
The optimal set of the properties of elastomeric glues can be achieved by the right ratio of components. The combined influence of resins, plasticizers and agents of tackiness on the properties of adhesive compositions was studied.